2008
DOI: 10.1890/08-0354.1
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Subsidies: Adult Stream Insects Export Organic Contaminants to Riparian Predators

Abstract: Aquatic insects provide a critical energy subsidy to riparian food webs, yet their role as vectors of contaminants to terrestrial ecosystems is poorly understood. We investigated relationships between aquatic resource utilization and contaminant exposure for a riparian invertivore assemblage (spiders and herptiles) along a stream contaminated with polychlorinated biphenyls (PCBs). Stable carbon (delta13C) and nitrogen (delta15N) isotopes indicated that aquatic insect utilization varied among predators, with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
194
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(209 citation statements)
references
References 32 publications
8
194
5
2
Order By: Relevance
“…We highlight the ways in which a new understanding of the aquatic-terrestrial interface has prompted an integrated view of cross-boundary contaminant flows within complex ecological networks. We pay particular attention to aquatic insects, which as an important source of energy for riparian consumers such as arthropods, birds, mammals, and reptiles, are especially likely to move contaminants into terrestrial ecosystems [4][5][6] (Fig. 1).…”
Section: Etandc Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight the ways in which a new understanding of the aquatic-terrestrial interface has prompted an integrated view of cross-boundary contaminant flows within complex ecological networks. We pay particular attention to aquatic insects, which as an important source of energy for riparian consumers such as arthropods, birds, mammals, and reptiles, are especially likely to move contaminants into terrestrial ecosystems [4][5][6] (Fig. 1).…”
Section: Etandc Focusmentioning
confidence: 99%
“…For example, using natural abundances of stable isotopes now allows scientists to track contaminant fluxes within and between ecosystems [13] and to predict exposure to riparian and terrestrial consumers [6]. Scientists also use the isotopic compositions of contaminants themselves to track the contribution of anthropogenic sources of contaminants in aquatic consumers.…”
Section: Understanding Processes Through Space and Timementioning
confidence: 99%
“…Emergent aquatic insects transport MeHg to nearby terrestrial habitats, potentially exposing terrestrial consumers to aquatic pollutants [3,4], the so called darkside of cross-system subsidies [5]. The flux of MeHg from aquatic environments to terrestrial environments is especially significant because MeHg is not normally produced in terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Because Hg concentrations are now elevated above baseline levels in all aquatic ecosystems due to widespread anthropogenic emissions and a dynamic global atmospheric cycle [6], it is important to understand the factors that control the emergence of aquatic insects and the movement of MeHg out of aquatic systems. Recent studies have demonstrated that aquatic insects biotransport MeHg and other contaminants to terrestrial consumers [e.g., 3,5,9], but the factors that regulate the flux of MeHg out of aquatic ecosystems via emergent insects have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether PBDEs in the aquatic compartment can also be transferred to the surrounding terrestrial environment is unclear. The aquatic to terrestrial transfer could be an important transport mechanism for POPs since they can move through the food web in a similar manner as nutrients and energy, bioaccumulate through the food chain and thereby posing an increasing risk to animals at the top of the food chain (Walters et al 2008). Furthermore, analysis of stable isotopes of e.g., carbon and nitrogen can be used to elucidate the structure of local food webs and is a very useful complementary tool to investigate the flow of organic matter and contaminants in the ecosystem (Jardine et al 2006).…”
Section: Introductionmentioning
confidence: 99%